STUDI ETNOBOTANI FAMILI ZINGIBERACEAE DALAM KEHIDUPAN MASYARAKAT LOKAL DI KECAMATAN SIAK HULU KABUPATEN KAMPAR - Annisa Auliani; Fitmawati '; Nery Sofiyanti (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
The local people from Siak Hulu, Kampar have traditional knowledge about the use of plant for medicinal purposes. One of plant family mainly used for medicinal plant is Zingiberaceae. This research aimed to investigate the use of Zingiberaceae for traditional medicine in Siak Hulu, Kampar. This research had been carried out from June 2012 toDecember 2013. A total of four study sites were selected. The herbarium and plant identification were prepared in the Laboratory of Botany, Department of Biology, Facultyof Mathematic and Natural Sciences. The result showed that 10 Zingiberaceae species used by local people in Siak Hulu for traditional medicine were Curcuma Domestica, Zingiberofficinale, Kaemferia galanga, Alpinia galanga, Zingiber cassumunar, Zingiber Americans, Alpinia zerumbet, Alpinia conchigera, Zingiber officinale var. rubrum. All of the specieswere herb type. It was also found that the common way in using the medicinal plant was by being pounded.